The reason Malaysian should take Islamic insurance (Takaful) in Prudential based on policyholder feedback / Noor Asyiqin Zakaria - Zakaria, Noor Asyiqin (Faculty of Business and Management, 2011)
This research is about a study of the reason Malaysian should take Islamic insurance (Takaful). For indicate concept of investment, business ethic and facilities (product) factor used to identifying the policyholder feedback towards Takaful product. The concept of investment consists of Shari’ah principles such as Ta’awun concept and Tabarru concept. Next, business ethic consists of keenness, mutual consent, truthfulness, trustworthiness, generosity, leniency, honouring and fulfilling. Last reason is facilities (product) factor consists of convenience such as compassionate benefit (funeral), Takaful hajj, zakat, and Takaful family. The survey is conducted in Prudential Bachang, Melaka. The sample size for this study is 100respondents. This study tries to investigate this issue by conducting a preliminary study on the policyholder feedback towards Takaful product. There were 100 respondents being distributed and 100 were return and complete. Data obtained using two methods that are primary data and secondary data and other data. Respondents are required to answer the questionnaires that contain element that needed for the research. Data are analyzed using Reliability Test, Pearson Correlation Analysis, Frequency Analysis, and Descriptive Statistics through SPSS system. The result shows what actually the most factors influences Malaysian to take Takaful from the policyholder feedback.